Survey of fruit nutrient removal by mango (Mangifera indica L.) cultivars for the export market in various producing regions of Mexico - Mellado-Vázquez, Adriana; Salazar-García, Samuel; Goenaga, Ricardo; López-Jiménez, Alfredo (REVISTA TERRA LATINOAMERICANA, 2019)
In Mexico there are more than 201 400 ha grown with different mango (Mangifera indica L.) cultivars. This may cause variations in mineral requirement, fruit mineral concentrations and nutrient removal. The objective of this research was to make a survey of mineral concentration in fruit tissues and calculate nutrient removal by fruit tissues during harvest of the most important mango cultivars (Ataulfo, Kent and Tommy Atkins) from several production regions (Campeche, Chiapas, Oaxaca, Nayarit, and Sinaloa) of Mexico. Fruit at physiological maturity were harvested from commercial mango orchards and concentration of nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), sulfur (S), iron (Fe), copper (Cu), manganese (Mn), zinc (Zn) and boron (B) was determined for skin, mesocarp, endocarp, and seed tissues. Each tissue was cut into thin slices and they were dehydrated in a forced air oven at 70 °C, after that, were pulverized and they were analyzed: nitrogen by semi-microKjeldahl digestion, phosphorus with the ascorbic acid method and the other nutrients with atomic absorption. The removal of nutrients was calculated considering the weight of the fruit and the content of nutrients in each tissue. Signif icant differences in the concentration of N, K, Mg, and Zn were found among cultivars and tissues. Concentration of P, S, Cu, and Mn in the skin, Ca, Cu, and Mn in the mesocarp, Ca, S, Mn, and B in endocarp, and S, Fe, and Mn in the seed were not affected by mango cultivar. Production region affected concentration of minerals in ‘Ataulfo’ fruit more than in ‘Tommy Atkins’ and ‘Kent’. Nutrient removal by mango fruit tissues was little affected in cvs. Ataulfo, Tommy Atkins and Kent. The regions with the greatest nutrient removal were Oaxaca, Campeche and Sinaloa for ‘Ataulfo’, ‘Tommy Atkins’ and ‘Kent’, respectively.